Thich Nhat Hanh : essential writings / edited by Robert Ellsberg ; introduction by Annabel Laity. - Nhất Hạnh, Thích. (Modern spiritual masters series., 2001)
"Drawn from more than twenty of his books, these are the essential writings of one of the most beloved and influential spiritual figures of our day."--BOOK JACKET.